Analisis Teknik Relaksasi dan Mobilisasi untuk Mengatasi Nyeri pada Ibu Post Sectio Caesarea (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of the Benson relaxation technique on the pain scale in post-SC surgery patients at RSU Proklik Karawang in 2023. The research method used pre-experiment with a research design of one group pre and post test design. The results of the research showed that there was a decrease in the average pain score before and after Benson relaxation by 6.13 on the pain scale and the results of the t-test showed that there was a significant difference in pain scores before and after Benson relaxation intervention in patients after caesarean section Sig. (2-tailed) of 0.000